Ultrasonography and management practices to understand pathogenesis and improve mitigation of fescue toxicosis and liver abscesses, and assess chute side diagnostics and prognostics of respiratory diseases in beef cattle - Barbosa Braga Feitoza, Luis Felipe (My University, 2024)
The objectives of the studies were to investigate three major ailments in the cattle industry: fescue toxicosis, liver abscesses, and respiratory diseases. A total of five studies were designed and conducted to determine utility of ultrasound and preventive measures to understand pathogenesis and prevention of fescue toxicity, prevention of liver abscesses, and evaluate chute side diagnostics and prognostics of respiratory diseases in cattle. In the first study, vasoactive compounds administered in low moisture, cooked molasses-based blocks were evaluated to mitigate fescue toxicosis and utilized ultrasonography to measure vascular diameter and assess blood perfusion to the periphery. Molasses-based block supplements with vasoactive compounds positively affected peripheral blood perfusion, improved thermoregulation and improved dry matter intake and average daily gain in cattle consuming ergot-infested tall fescue. In the second prospective study, strategic targeted durations of feeding tylosin phosphate at 60 mg animal per day for the first 30 or 60 days of the finishing phase on the incidence and severity of liver abscesses, performance and carcass characteristics were evaluated in feedlot cattle. Incidence of liver abscesses, overall cattle performance and carcass characteristics were not significantly affected by tylosin phosphate, however, a trend towards reduced severity of liver abscesses and increased body weight was observed. Three observational studies were conducted to assess the utility of targeted thoracic ultrasonography for diagnosis of interstitial pneumonia, prognosis with respiratory disease treatments, and feedyard outcomes. In a cross-sectional study that targeted thoracic point-of-care ultrasound of caudodorsal right lung in feedlot cattle, a significant associations of ultrasound scores and days on feed at treatment with interstitial pneumonia were observed. The second study aimed to determine associations between negative outcomes (culled or died) and point-of-care evaluations of feedlot cattle with chronic respiratory disease. Among the parameters evaluated, only ultrasound variables were significantly associated with negative outcomes of mortality or culling. The third was a cross-sectional observational study that evaluated point-of-care chut side diagnostics at the time of respiratory disease treatment to assess the likelihood of first treatment failure and negative outcomes. Variables significantly associated with did not finish (culled or died ) and first treatment failure include ultrasound scores, days on feeding, and body weights. The study identified key pulmonary and cattle demographic factors at chute side that valuable potential prognostic parameters when cattle are treated for respiratory disease. In conclusion, the current research on beef cattle collectively advances our understanding of cattle health management by highlighting preventive and management practices and the use of chute side diagnostic tools that can impact cattle outcomes. The integration of targeted diagnostics, such as thoracic ultrasonography, into routine management practices can significantly enhance prognosis accuracy and help with respiratory disease differentiation, optimize treatment decisions, and improve overall animal welfare. These findings not only offer practical applications for beef cattle operations but also provide a foundation for future research aimed at further refining cattle health management strategies and improving economic outcomes and animal welfare in the industry.
Keywords: Fescue toxicity; Beef cattle; Liver abscesses; Respiratory diseases; Ultrasonography; Animal health